Reading Bibles, writing bodies : identity and the Book - Beal, Timothy K. (Timothy Kandler), 1963-; Gunn, D. M. (David M.) (1997)
The Bible, a religious text, is also often said to be one of the foundation texts of Western culture. The present volume explores how religious, political and cultural identities, including ethnicity and gender, are embodied, often problematically, in biblical discourse. Following the authors, we read the Bible with new eyes: as a critic of gender, ideology, politics, and culture. We ask ourselves new questions: about God's body, about women's roles, about racial prejudices and about the politics of the written word
Opening: Cracking the Binding / Timothy K. Beal -- 1. Shifting the Blame: God in the Garden / Danna Nolan Fewell and David M. Gunn -- 2. The Problem of the Body for the People of the Book / Howard Eilberg-Schwartz -- 3. The Hebrew God and His Female Complements / Athalya Brenner -- 4. Oedipus Wrecks: Moses and God's Rod / Ilona N. Rashkow -- 5. Woman Wisdom and the Strange Woman: Where is Power to be Found? / Claudia V. Camp -- 6. Woman and the Discourse of Patriarchal Wisdom / Carol A. Newsom -- 7. Imagination, Method, and Murder: Un/Framing the Face of Post-Exilic Israel / Danna Nolan Fewell -- 8. The Problem with Pagans / L. Daniel Hawk -- 9. Assuming the Body of the Heir Apparent: David's Lament / Mark K. George -- 10. Utopia and Pornography in Ezekiel: Violence, Hope, and the Shattered Male Subject / Jan William Tarlin -- 11. "An Imaginary and Desirable Converse": Moses and Monotheism as Family Romance" / Daniel Boyarin
Includes bibliographical references (pages 262-276) and indexes
Keywords: Bible. -- Hermeneutics; Bible. -- Criticism, interpretation, etc; Bible. -- Feminist criticism; Human body -- Biblical teaching; Bible as literature; Criticism, interpretation, etc; Aufsatzsammlung